Perkaitan Di Antara Iklim Dan Disiplin Organisasi Pembelajaran dalam Organisasi Awam di Sarawak - Herni, Suhaimi (Universiti Malaysia Sarawak (UNIMAS), 2004)
Generally this research is to identify relationship between level of organizational climate and level of learning organization in the public organization in Sarawak. It also ascertains whether there is a difference in perception towards level of learning organization discipline base on demographic factor like sex and service group. A total of 38 employees were chosen as respondents at PUSTAKA. Selections of respondents were base on randomly stratified sampling technique. A questionnaire was use as an instrument for the study. Program SPSS version I1 was used to analyze data. Statistic method like descriptive analysis, correlation, 1-test, one way anova and regression analysis was used to get the result of research analysis. Research result indicated that the level of Learning Organization discipline is at the higher level same as the level of organization climate also at the higher level. The respondents also show that the both the climate and Learning Organization discipline have a medium and positive relationship that are at level of r=0.432. Sex. factor gives significant difference towards the Learning Organization discipline. Whereas the service group do not show any significant difference towards the Learning Organization discipline. Due to the fact that there is medium relation between climate and the level of the Learning Organization discipline, it is therefore suggested that the organization administration should take proper steps against the weaknesses in reaction to the organization climate to enhance the level of organization climate